Analisis dampak program makan bergizi gratis terhadap risiko pembiayaan bank syariah di Indonesia melalui peningkatan aktivitas sektor ekonomi - aulia, keysya valentina (Maliki Interdisciplinary Journal, 2026)
The Free Nutritious Meal Program (MBG) is a government policy aimed at improving human resource quality while simultaneously encouraging economic growth, particularly in the food, distribution, and micro, small, and medium enterprise (MSME) sectors. The implementation of this program is expected to increase economic activity, which in turn drives financing demand from financial institutions, including Islamic banks. However, the growth in financing may also lead to banking risks, especially financing risk reflected in Non-Performing Financing (NPF). This study aims to examine the impact of the Free Nutritious Meal Program on Islamic bank financing risk in Indonesia through increased economic sector activity. This research employs a qualitative approach using a literature review method by analyzing various journals related to the MBG program, economic sector development, MSMEs, and Islamic banking risk management from general journals and UIN Malang journals. The findings indicate that the MBG program has the potential to stimulate economic activity and expand Islamic bank financing in the food and MSME sectors, while also increasing financing risk due to dependence on government policies, unstable business income, and the possibility of non-performing financing. Therefore, Islamic banks need to adopt adaptive risk management strategies to maintain financial stability. This study contributes to understanding the relationship between government policy and Islamic banking risk in supporting national economic resilience.